2011
DOI: 10.1097/meg.0b013e3283435d76
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hepatorenal syndrome in patients with cirrhosis and ascites

Abstract: Pentoxifylline is effective in preventing HRS in patients with cirrhosis and ascites at risk of HRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…interleukin-6, tumor necrosis factor-alpha) and endotoxins. 85 These findings are in line with studies that showed beneficial effect of pentoxifylline, a tumor necrosis factor-alpha synthesis inhibitor, in reversing HRS in patients with severe alcoholic hepatitis 86 and preventing HRS 87 and renal insufficiency 88 in those with cirrhosis. 85 Like other manifestations of acute on chronic liver failure, proinflammatory mechanisms may play a significant role in the pathogenesis of HRS.…”
Section: Pathophysiology Of Hrssupporting
confidence: 84%
“…interleukin-6, tumor necrosis factor-alpha) and endotoxins. 85 These findings are in line with studies that showed beneficial effect of pentoxifylline, a tumor necrosis factor-alpha synthesis inhibitor, in reversing HRS in patients with severe alcoholic hepatitis 86 and preventing HRS 87 and renal insufficiency 88 in those with cirrhosis. 85 Like other manifestations of acute on chronic liver failure, proinflammatory mechanisms may play a significant role in the pathogenesis of HRS.…”
Section: Pathophysiology Of Hrssupporting
confidence: 84%
“…There are several potential limitations of the present study that should be addressed. Firstly, pentoxifylline has been found to have novel biochemical effects, including the alleviation of renal vasoconstriction ( 23 ), reduction of oxidative stress and modulation of inflammatory responses ( 24 ). These properties may also be used to prevent CIAKI as proposed by Roozbeh et al ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline is a phosphodiesterase inhibitor with beneficial effects on renal function. Tyagi et al performed a randomised controlled trial involving 70 patients with cirrhosis, ascites, and a baseline normal renal function [ 79 ]. Patients were randomised into two treatment arms, pentoxifylline or placebo.…”
Section: Prophylaxismentioning
confidence: 99%